An empirical investigation on the impact of capital structure on firm performance: evidence from Malaysia. Issue 8 (30th March 2021) - Ayaz, Muhammad; Mohamed Zabri, Shafie; Ahmad, Kamilah
Abstract : Purpose: The purpose of this study is to examine the relationships between leverage and firm's performance in Malaysia by framing the relationship under the tradeoff theory and agency cost theory. Design/methodology/approach: Based on insights drawn from the existing literature, we opted for fixed effects and system two-steps GMM models to establish the hypothesized relationship between leverage and performance. We analyzed 528 nonfinancial firms listed on the Bursa Malaysia Stock exchange for the period of 12 years (2005–2016). Findings: The outcomes show that the leverage ratio improves the firm performance, consistent with leverage serving as an effective strategy in constraining managers from building their personal empire, revealing a proportionately greater benefit for Malaysian firms than the cost to debt financing. The authors also find that a positive relationship between leverage and firm performance switch to the negative when the level of leverage reaches beyond the optimal level. Consequently, switching from positive to negative indicates that debt has a twofold (nonlinear) impact on firm performance. Practical implications: Our research provides several implications to potential stakeholders. For investors, firms having lower leverage ratios could achieve superior performance, thus investing in corporations pursuing higher performance. Managers should therefore strive for achieving higher performance to meet the needs of investors and shareholders. From the researcher's perspective, our research suggests the need to go away from the searching linear association between leverage and firm performance and the relevance of nonlinear correlation. Moreover, our research can help managers to understand how their lender relates to their debt to assets ratios. Thus, they can design an optimal level of leverage that not only improves the firm's performance but also reduce the associated costs. Originality/value: To the best of the author's knowledge, this is the initial attempt in the context of Malaysia that documents evidence indicating that the lower leverage is likely to create value for shareholders while a higher debt ratio reduces firm profitability.